Dynamic ferroelectric hysteresis scaling of BaTiO3 single crystals - N. Wongdamnern (2018)
The scaling behavior of the dynamic hysteresis of ferroelectric BaTiO3 single crystals was investigated. Two sets of the scaling relation of hysteresis area 〈A〉 against frequency f and field amplitude E0 were clearly established. Above the coercive field, the scaling took a form of 〈A〉 f-0.195 E0 0.950. On the other hand, the scaling in the form of 〈A〉 f1.667 E0 -2.804 E0 4.157 was obtained under subcoercive field condition. While these scaling relations were generally comparable to previously reported ones, it was found that the f and E0 exponents depended on E0 and f, respectively, which was in contrast to the prior theoretical prediction and experimental investigations. © 2009 American Institute of Physics.